The impact of environmental disclosure on financial performance indicators of Iraqi industrial companies - Al-Waeli, Abbas Jumaah Jayed (2023)
The main aim of this study is to determine the influence of environmental disclosure on financial performance of Iraqi industrial companies. This is because of the Iraqi Companies Law did not required for certain industries such as industrial companies to disclose their environmental information in annual reports. Furthermore, instability of the Iraq political system and exposure to a war also dedicated to less information disclosure practices in Iraqi companies. All these factors have been observed to significantly influences on the industrial companys performance. A Legitimacy Theory has been adopted to explore the relationship between environmental disclosure and financial performance, using quantitative approach and purposive sampling was utilized as the main research design. The data was collected from 25 manufacturing companies listed on the Iraq Stock Exchange (ISX) and the oil sector from 2015 to 2019. The data was analyzed through descriptive statistics, univariate statistics, regression analysis and content analysis of the companies annual reports using Eviews. The main results showed environmental disclosure (= 0.265, p-value <0.05) positively influenced Return on Assets (ROA). Also, extended analysis showed a positive impact of environmental disclosure (=0.0369, p-value <0.05) on Return on Investment (ROI). However, the finding also revealed that environmental disclosure (= 0.158, p-value <0.05) was positive and significant in affecting Return on Sales (ROS). It was found that environmental disclosure is fully affected (=0.305, p-value <0.05), and had positive effects on Added Market Value (AMV). Nonetheless, environmental disclosure had a negative impact on Earnings Per Share (EPS) (= 0.496, p-value <0.05). These results suggest that a high-sensitive industry towards the environmental issues provide more disclosure to boost investors' confidence. The study's outcomes provide insights view-related environmental disclosure among the sensitive industries that relate to legitimacy issues in Iraq. Moreover, improving the quality of reporting would increase the companys reputation and strengthen its competitiveness. This contributes to the adoption of a developed checklist mechanism to measure the true level of environmental disclosure.